A Recommender System for YouTube Video based on deep neural network - Singh, Rashmi; Vijaykumar, Suhasini (International Journal of Computer Sciences and Engineering, 2019)
YouTube is video sharing sites where a user can create own profile, upload videos and watch the multiple videos. The YouTube uses the recommender system. With the help of recommendation system we boost the popularity of videos. The recommendation is based on the relation between the number of views and the average number of views on particular videos. The recommendation also considers the likes and comment section. When the viewers view the same type of video then YouTube recommends the same type of video. The YouTube recommendation is based on machine learning technique. In machine learning we used the concept of the deep learning method. With the help of deep learning we solve the sophisticated problem. In this paper we see the working of deep neural network to recommend the video based on viewers.